2018
DOI: 10.1002/ejic.201800490
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Methanol Oxidation by Supported Vanadium Oxide Species: Influence of Support and Degree of Oligomerization

Abstract: Supported isolated vanadium oxide (VO 4 ) species on silica have recently been shown to photocatalytically oxidize methanol selectively to formaldehyde. Insights into support effects and the reactivity of the different supported vanadium oxide species in photocatalytic methanol oxidation are obtained in the present study by varying the support, surface vanadium oxide loading, and synthesis procedure. Isolated and oligomeric surface vanadium oxide species supported on alumina can also photocatalytically oxidize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 80 publications
1
5
0
Order By: Relevance
“…At 250°C, a small band at 2896 cm À 1 appears and it is probably associated to symmetrical CÀ H stretching of surface formate species (HCOO À ) generated by the re-adsorption of the formaldehyde produced during the reaction. [49] In the low wavenumber region ( Figure S8), bands at 1434 and 1451 cm À 1 , related to symmetric and asymmetric deformation modes of methoxy species, [49] and at 1745 cm À 1 related to C=O stretching of molecularly adsorbed formaldehyde, [50] confirmed the observations of high wavenumber spectra. Considering that intensities are proportional to the concentration of species adsorbed on surface, [51] the evolution of adsorbed methanol on the silica surface and methoxy species on V sites were monitored by band intensities at 2958 and 2933 cm À 1 , respectively, during methanol flow for 30 min, and the results are shown in Figure 6D.…”
Section: Resultssupporting
confidence: 76%
“…At 250°C, a small band at 2896 cm À 1 appears and it is probably associated to symmetrical CÀ H stretching of surface formate species (HCOO À ) generated by the re-adsorption of the formaldehyde produced during the reaction. [49] In the low wavenumber region ( Figure S8), bands at 1434 and 1451 cm À 1 , related to symmetric and asymmetric deformation modes of methoxy species, [49] and at 1745 cm À 1 related to C=O stretching of molecularly adsorbed formaldehyde, [50] confirmed the observations of high wavenumber spectra. Considering that intensities are proportional to the concentration of species adsorbed on surface, [51] the evolution of adsorbed methanol on the silica surface and methoxy species on V sites were monitored by band intensities at 2958 and 2933 cm À 1 , respectively, during methanol flow for 30 min, and the results are shown in Figure 6D.…”
Section: Resultssupporting
confidence: 76%
“…125 Besides, Strunk et al investigated the effects of supported vanadium oxide species and degree of oligomerization on photocatalytic methanol oxidation. 126 Fang and co-workers reported a Cu−V bimetallic catalyst (CuVO x ) catalyzed heterogeneous Fenton process for the degradation of fluconazole. 127 It was found that this novel catalyst had higher catalytic activity and better reusability than those of monometallic Cu compounds.…”
Section: Oxidationmentioning
confidence: 99%
“…It was proposed that the difference was related to the activation energy for the C–H bond cleavage of the V–OCH 3 . Besides, Strunk et al investigated the effects of supported vanadium oxide species and degree of oligomerization on photocatalytic methanol oxidation …”
Section: Organic Synthesismentioning
confidence: 99%
“…13 such hydrated conditions, vanadia is known to interact with adsorbed moisture, stimulating a structural change as a thin aqueous layer forms on the oxide support that enables vanadia to migrate and form new molecular structures. 14 To obtain a detailed molecular picture of these structures of vanadium oxide supported on titania under such conditions, nuclear magnetic resonance (NMR) was exploited as a tool to discriminate and quantify the vanadia species present on hydrated supported vanadium oxide catalytic materials.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Hydration is of particular interest because of its relevance to the initial state of manufactured catalysts prior to their use and to the photocatalytic performance of vanadium-based heterogeneous catalysts because water molecules are not driven from the surface under ambient conditions . Under such hydrated conditions, vanadia is known to interact with adsorbed moisture, stimulating a structural change as a thin aqueous layer forms on the oxide support that enables vanadia to migrate and form new molecular structures . To obtain a detailed molecular picture of these structures of vanadium oxide supported on titania under such conditions, nuclear magnetic resonance (NMR) was exploited as a tool to discriminate and quantify the vanadia species present on hydrated supported vanadium oxide catalytic materials.…”
Section: Introductionmentioning
confidence: 99%